2017
DOI: 10.5489/cuaj.4132
|View full text |Cite
|
Sign up to set email alerts
|

Study habits of Canadian urology residents: Implications for development of a competence by design curriculum

Abstract: Introduction: The purpose of this study was to evaluate the study habits of Canadian urology residents throughout their residency training. Methods: A survey was administered to all final-year Canadian urology residents over a two-year period. Sixty-seven respondents answered a survey consisting of 54 questions scored on a 10-point Likert score. The survey addressed study habits throughout training, motivations for studying, and preferred resources used. Results: Dedication to studying was directly correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 13 publications
1
21
1
Order By: Relevance
“…In our study, independent study showed higher percentages of acceptance among urology residents (Figure 4), which corroborates the result from Canadian urology residents 3 but opposes Boehler et al 18 findings that group study results in higher achievement rates among third-year American medical students. In our study, group study and dedicated lectures were the least preferred methods for both groups.…”
Section: Methods Of Study During Residencysupporting
confidence: 90%
See 3 more Smart Citations
“…In our study, independent study showed higher percentages of acceptance among urology residents (Figure 4), which corroborates the result from Canadian urology residents 3 but opposes Boehler et al 18 findings that group study results in higher achievement rates among third-year American medical students. In our study, group study and dedicated lectures were the least preferred methods for both groups.…”
Section: Methods Of Study During Residencysupporting
confidence: 90%
“…Most Saudi urology residents (82.3%) reported studying up to 10 hours per week (Table 2), which exceeds the 4 hours for surgical residents 5 but is less than the 10 hours for Canadian urologists. 3 In our study, juniors read more than seniors (P = 0.034) ( Figure 2). On the contrary, chief residents (PGY5) in Canada read 96% more per week than junior residents (PGY1, PGY2) and senior residents (PGY3, PGY4).…”
Section: Study Habits and Residents' Performancementioning
confidence: 53%
See 2 more Smart Citations
“…The incidence of infertility has increased annually, and the current worldwide incidence of infertility has reached 15% (7). The proportion of male factors contributing to this problem is approximately 50% (8). Semen analysis indicators are now used to assess male fertility, and the main reasons for infertility are reduced sperm number and decreased sperm viability.…”
Section: Discussionmentioning
confidence: 99%